Comparative Study of TiO2 and CdS as the Electron Transport Layer for Sb2S3 Solar Cells. Issue 10 (15th August 2022) - Zeng, Yiyu; Huang, Jialiang; Li, Jianjun; Sun, Kaiwen; Shah, Usman Ali; Deng, Hui; Zhang, Xueyun; Sha, Chuhan; Qian, Chen; Song, Haisheng; Hao, Xiaojing
Abstract : Antimony sulfide (Sb2 S3 ) is a promising wide‐bandgap photovoltaic material, and a potential top‐cell candidate for next‐generation Si‐based tandem solar cells. The most widely used electron transport layers in Sb2 S3 solar cells are TiO2 and CdS, which present an obvious performance variation in open‐circuit voltage ( V OC ) and short current ( J sc ). However, the mechanisms behind the performance disparity because of the electron transport layer (ETL) have not been disclosed. Herein, a comprehensive comparative study of using TiO2 and CdS as the electron transport layers in Sb2 S3 solar cells is presented, which covers their influence on preferential crystal orientation, band alignment, interface, and bulk defects. It is found that the CdS ETL results in less interfacial defects and more favorable band alignment, enabling a higher V OC, while the high resistance of the CdS film and parasitic light absorption restricts the J SC . The findings provide a substantial guidance on device optimization for Sb2 S3 solar cells. Abstract : The preferred [ hk 1]‐orientated Sb2 S3 ribbons are supposed to improve the device performance by facilitating the carrier transport and reducing the interface and bulk defects. The texture coefficients of (121) and (221) of CdS/Sb2 S3 are much higher than those of TiO2 /Sb2 S3 film, indicating preferred [ hk 1] grain orientations of Sb2 S3 are easier to attain via depositing on the CdS layer.